Berry Phenolic Antioxidants – Implications for Human Health? - Olas, Beata (Frontiers in Pharmacology, 2018)
Antioxidants present in the diet may have a significant effect on the prophylaxis and progression of various diseases associated with oxidative stress. Berries contain a range of chemical compounds with antioxidant properties, including phenolic compounds. The aim of this review article is to provide an overview of the current knowledge of such phenolic antioxidants, and to discuss whether these compounds may always be natural gifts for human health, based on both in vitro and in vivo studies. It describes the antioxidant properties of fresh berries (including aronia berries, grapes, blueberries, sea buckthorn berries, strawberries and other berries) and their various products, especially juices and wines. Some papers report that these phenolic compounds may sometimes behave like prooxidants, and sometimes demonstrate both antioxidant and prooxidant activity, while others note they do not behave the same way in vitro and in vivo. However, no unwanted or toxic effects (i.e. chemical, hematological or urinary effect) have been associated with the consumption of berries or berry juices or other extracts, especially aronia berries and aronia products in vivo, and in vitro, which may suggest that the phenolic antioxidants found in berries are natural gifts for human health. However, the phenolic compound content of berries and berry products is not always well described, and further studies are required to determine the therapeutic doses of different berry products for use in future clinical studies. Moreover, further experiments are needed to understand the beneficial effects reported so far from the mechanistic point of view. Therefore, greater attention should be paid to the development of well-controlled and high-quality clinical studies in this area.